2001
DOI: 10.1073/pnas.041613598
|View full text |Cite
|
Sign up to set email alerts
|

Reverse engineering the (β/α) 8 barrel fold

Abstract: The (␤͞␣)8 barrel is the most commonly occurring fold among protein catalysts. To lay a groundwork for engineering novel barrel proteins, we investigated the amino acid sequence restrictions at 182 structural positions of the prototypical (␤͞␣)8 barrel enzyme triosephosphate isomerase. Using combinatorial mutagenesis and functional selection, we find that turn sequences, ␣-helix capping and stop motifs, and residues that pack the interface between ␤-strands and ␣-helices are highly mutable. Conversely, any mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 24 publications
5
80
1
Order By: Relevance
“…4 Several researchers have demonstrated that the amino acid usage of various natural globular proteins and enzymes can be restricted to 5-13 members without substantial alteration of their structures and biological functions. [5][6][7][8] Riddle et al simplified the sequence of a small b-sheet protein, the SH3 domain, by using phage display selection, and produced two SH3 variants in which 90% of the sequence, excluding the binding region, utilized only five amino acids (Ala, Gly, Glu, Ile, and Lys). 5 Silverman et al generated variants of the prototypical (b/a) 8 barrel enzyme, triosephosphate isomerase (TIM), in which the amino acids at 142 of 182 structural positions were simplified to seven kinds (Ala, Glu, Val, Lys, Phe, Leu, and Gln) by means of in vivo selection for TIM activity.…”
Section: Introductionmentioning
confidence: 99%
“…4 Several researchers have demonstrated that the amino acid usage of various natural globular proteins and enzymes can be restricted to 5-13 members without substantial alteration of their structures and biological functions. [5][6][7][8] Riddle et al simplified the sequence of a small b-sheet protein, the SH3 domain, by using phage display selection, and produced two SH3 variants in which 90% of the sequence, excluding the binding region, utilized only five amino acids (Ala, Gly, Glu, Ile, and Lys). 5 Silverman et al generated variants of the prototypical (b/a) 8 barrel enzyme, triosephosphate isomerase (TIM), in which the amino acids at 142 of 182 structural positions were simplified to seven kinds (Ala, Glu, Val, Lys, Phe, Leu, and Gln) by means of in vivo selection for TIM activity.…”
Section: Introductionmentioning
confidence: 99%
“…A common biological structural motif is that of the ␣-helix, and subsequently much de novo design utilizes this scaffold, although ␤-sheets and mixed ␣/␤-constructs have also been investigated (4,(9)(10)(11). Work in our group involves the designed TRI and GRAND peptides based on the heptad repeat, L a K b A c L d E e E f K g , and derivatives thereof (12,13).…”
mentioning
confidence: 99%
“…Therefore, to design the proteins based on a simplified alphabet would provide a way to check the validity of the simplified alphabet. This kind of idea has been realized in many experiments [56][57][58][59][60][61][62][63]. Facing with the helix bundles, de novo designs were realized based on hydrophobic/polar patterns along the protein chains [56,57].…”
Section: Simplification Based On Design Experimentsmentioning
confidence: 99%
“…To reproduce the catalytic activity, more types of amino acids are needed. Through sophisticated designs and selections, active enzymes could be constructed from 9-amino-acid alphabets [61][62][63]. It reflects that there are more demands with further function requirements.…”
Section: Simplification Based On Design Experimentsmentioning
confidence: 99%